2016
DOI: 10.1007/s10735-016-9678-z
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of CtBP1 suppresses the migration in human glioma cells

Abstract: Carboxyl-terminal binding protein 1 (CtBP1), up-regulated in various types of human cancers, has been functionally associated with proliferation, anti-apoptosis, and EMT in vitro studies. However, the functional significance of CtBP1 in the pathophysiology of glioma remains unknown. In the present study, we showed the expression of CtBP1 was markedly higher in glioma tissues compared with normal brain tissues by Western blot analysis. Immunohistochemical analysis revealed that CtBP1 mainly localized in the nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
2
12
1
Order By: Relevance
“…GC was reported to rank the second leading cause of cancer-specific mortality worldwide.31 With a poor prognosis, 5-year survival rate of GC is less than 20–25% in the USA, China, and Europe.32 However, early GC represents an excellent (over 90%) opportunity of cure through surgical resection.2 As the increasing detection of early GC, biological therapy options have been technologically advanced both curatively and minimally invasively to maintain a good quality of life 1,3. Recently, dysregulated control of CtBPs expression have been revealed to be a vital originating step in the formation of certainhuman tumors 3335. CtBPs inhibit multiple proapoptotic and epithelial genes, and overexpression of CtBP in human cancer cells promotes the EMT and cancer cell survival 15,16,36.…”
Section: Discussionmentioning
confidence: 99%
“…GC was reported to rank the second leading cause of cancer-specific mortality worldwide.31 With a poor prognosis, 5-year survival rate of GC is less than 20–25% in the USA, China, and Europe.32 However, early GC represents an excellent (over 90%) opportunity of cure through surgical resection.2 As the increasing detection of early GC, biological therapy options have been technologically advanced both curatively and minimally invasively to maintain a good quality of life 1,3. Recently, dysregulated control of CtBPs expression have been revealed to be a vital originating step in the formation of certainhuman tumors 3335. CtBPs inhibit multiple proapoptotic and epithelial genes, and overexpression of CtBP in human cancer cells promotes the EMT and cancer cell survival 15,16,36.…”
Section: Discussionmentioning
confidence: 99%
“…CTBP1/BARS and its downstream target PLD1 , whose activation triggers the closure and the final fission of macropinosomes from the plasma membrane [9,61,62], were found downregulated in high-grade tumors at the mRNA level herein. Those results are not consistent with previous data indicating positive correlation of Ctbp protein antigen expression with the histopathologic grade of the glioma [63] and worse survival of the patient [64]. The discrepancies could be related to evaluation at the mRNA versus protein expression level.…”
Section: Discussioncontrasting
confidence: 92%
“…We also found that CTBP1 protein increased the migratory capability of TNBC MDA-MB-231 and 4T1 cells. These results support previous studies showing that CTBP1 increases migration of hormone sensitive MCF-7 BrCa cells [ 18 ] and other cell types such as glioma cancer cells [ 20 ].…”
Section: Discussionsupporting
confidence: 92%